A STUDY ON THE REALITY OF ORGANIZATIONAL AGILITY LEVEL OF SPECIALIZED SUPERVISORS AND ITS RELATIONSHIP TO THE OPERATIONAL PROFICIENCY OF PHYSICAL EDUCATION TEACHERS IN MAYSAN GOVERNORATE - Mohammed, Jasim Ali; Yasin, Mustafa Ismail (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. The research problem emerged from the existence of a discrepancy between the continuity and speed of field variables and challenges faced by physical education teachers, and the slow administrative response in finding solutions to some real problems by specialized supervisors in the General Directorate of Education in Maysan. This situation casts its shadow on the work of physical education teachers in Maysan schools and affects their operational competence in utilizing available resources and exploring solutions to address the problems and challenges that hinder their work and impede the achievement of physical education lesson objectives. Objectives. This study aims to highlight the reality of organizational agility among physical education supervisors in the Maysan Governorate Center and its relation to the operational competence of physical education teachers. This is done by designing and applying two tools to measure these two phenomena, assessing their levels from the teachers' perspective, and then determining the relationship between them. Method. The researcher used the descriptive method with a correlational approach due to its suitability for the nature of the study problem and its appropriateness for achieving its objectives, on a study sample of physical education teachers from schools in the center of Maysan Governorate, totaling (184) teachers, selected randomly by the researcher from a total population of (350) teachers, representing (51.4%) of it. The sample was divided into three main groups: (14) teachers for the exploratory sample, (100) teachers for building the two scales, and (70) teachers for applying them. After building and applying the Organizational Agility Scale, which included (24) items distributed across three dimensions, and the Operational Proficiency Scale with (20) items distributed across two dimensions, and analyzing their results statistically, extracting their validity, reliability, and relevance, and then discussing them, the researcher was able to achieve the study's objectives and draw the research conclusions. Results. Among the most important conclusions were: the supervisors of the specialty enjoyed a high level of organizational agility; physical education teachers had a good level of operational proficiency; and the higher the level of organizational agility of the supervisors, the higher the level of operational proficiency of the physical education teachers. Conclusion. The researcher also recommended making efforts by senior administrations and school administrations to provide a school environment that encourages teachers to experiment and innovate in practical lessons, and to work on providing all the necessary resources and communication channels to improve and enhance communication between supervisors and teachers, and to circulate the results of this study to all general directorates of education in the governorates to benefit from its results.